The complete mitochondrial genome of Thereuopoda clunifera (Chilopoda: Scutigeridae) and phylogenetic implications within Chilopoda - Zhao, Xinyi; Lu, Yifan; Fan, Shiming; Xu, Wei; Wang, Jiachen; Wang, Guobing; Liu, Hongyi (Zootaxa, 2022)
We determined the complete mitochondrial genome of Thereuopoda clunifera (Chilopoda: Scutigeridae) to clarify the phylogenetic status within Chilopoda. Using Sanger sequencing and next-generation sequencing technologies, the entire mitogenome of T. clunifera was assembled and annotated, with 14,898 bp in length and 37 genes (13 protein-coding genes, 22 transfer RNA genes, and two ribosomal RNA genes), which are usually found in arthropod mitogenomes. Only one D-loop contained no repeat element. The base composition of T. clunifera was found to be A + T content of 69.55% and G + C content of 30.45%. The AT-skew of T. clunifera was positive, while the GC-skew was negative. The gene order of T. clunifera was identical to that of Scutigera coleoptrata that has been unique among those so far determined for the Arthropoda. We also performed phylogenetic analyses of 25 Myriapoda species to further explore the taxonomic and evolutionary relationships within Myriapoda and Chilopoda. Phylogenetic analyses supported that the division of Chilopoda into subclasses Notostigmophora and Pleurostigmophora.